[Fe(bipy)Cl4][bipy.H] hosted by Al-MCM-41: an efficient dibenzo[b, f][1, 4]oxazepine (CR) decontamination nano-reactor. Issue 41 (7th May 2015) - Khorshidi, Alireza; Heidari, Sirous
<x xml:space="preserve">Abstract</x> Encapsulation of [Fe(bipy)Cl4][bipy.H] (1) (where bipy is 2, 2′-bipyridine) in the Al-MCM-41 molecular sieve by using a "ship in a bottle synthesis" approach was achieved and the product was used as a nano-reactor in selective oxidation reactions.